ASSESSMENT OF APPLICATION OF CONFLICT MANAGEMENT TECHNIQUES IN PUBLIC SECONDARY SCHOOLS ADMINISTRATION IN IKOM EDUCATION ZONE OF CROSS RIVER STATE, NIGERIA - Charles Ekpung (International Journal of Business, Law and Political Science, 2025)
Objective: This study investigated the application of conflict management techniques in public secondary schools in Ikom Education Zone of Cross River State, focusing on teachers, principals, and school supervisors. Method: Guided by three objectives, research questions, and hypotheses, the research adopted a descriptive survey design with a population of 1,630 respondents and a sample of 959 participants, comprising 299 teachers, 36 principals, and 30 supervisors. Data were collected electronically through a validated questionnaire, which achieved a reliability index of 0.79 using Cronbach’s Alpha. Frequency counts and simple percentages were used for bio-data analysis, while One Way Analysis of Variance (ANOVA) tested the hypotheses at a 0.05 significance level. Results: Findings revealed that all three null hypotheses were retained, indicating no statistically significant differences in the application of conflict management techniques across the respondent groups. Novelty: The study contributes to the discourse on conflict management in Nigerian secondary schools by highlighting the importance of teachers as role models and moral guides, emphasizing the need for equitable treatment of students, accessibility for guidance, and engaging pedagogical practices to foster harmonious school environments.